Phytochemical analyses of belalai gajah (Clinacanthus nutans Burm. f. Lindau) leaves butanol fraction - Zolkeflee, Nur Khaleeda Zulaikha (2018)
Clinacanthus nutans is a medicinal shrub that has been increasingly used as an antiviral regimen treatment in the form of water decoction or infusion. However, there are very few reports on phytochemical constituent studies focus on the polar fraction of this plant. Therefore, the aim of this study was to isolate and identify the phytochemical constituents present in the butanol fraction of the methanolic extract from the leaves of C. nutans. The butanol fraction was analyzed by LC-DADESIMS/ MS and twenty-eight compounds were tentatively identified including five types of apigenin derived compounds, two types of luteolin derived compounds, seven sulphur-containing compounds, three caffeoyl derived compounds and two other metabolites, named methyl 2-[cyclohex-2-en-1-yl(hydroxy)methyl]-3-hydroxy-4-(2- hydroxyethyl)-3-methyl-5-oxoprolinate (137) and 3,3-di-O-methylellagic acid (138). The tentatively identified compounds from apigenin derivatives were vicenin 2 (164) with its two isomers, isoschaftoside (168), schaftoside (11), neoschaftoside (169), gendarucin A (136) with its isomer, isovitexin (10), vitexin (9) and apigenin (145). The compounds identified from luteolin derivatives were isoorientin (14), orientin (13) and isoorientin 2”-O-apiofuranoside (146). The sulphur-containing compounds named clinacoside A (15), clinacoside B (16), clinamide E (44), clinacoside C (17), cycloclinacoside A1 (18), entadamide A (36) and clinamide B (33) were also tentatively identified in the butanol fraction. Caffeoyl derivatives, forsythoside A/H/I (165/166/167) were identified from the same fraction, together with methyl 2- [cyclohex-2-en-1-yl(hydroxy)methyl]-3-hydroxy-4-(2-hydroxyethyl)-3-methyl-5 oxoprolinate (137) with its isomer and 3,3-di-O-methylellagic acid (138) with its isomer. Identification of compounds from LC-DAD-ESIMS/MS data was supported by the literatures and MS databases. Subsequently, the fractionation and isolation of compounds from the butanol fraction were performed by various chromatography methods, including centrifugal partitioning chromatography (CPC), column chromatography and recycling high performance liquid chromatography (R-HPLC).Isolation of the butanol fraction of the methanolic C. nutans extract yielded seven compounds including isoorientin (14), orientin (13), schaftoside (11), isovitexin (10), vitexin (9), clinacoside B (16) and clinamide E (44). The structures of the isolated compounds were characterized based on collections of physical, spectroscopic (NMR and MS) data as well as comparison with literatures. In conclusion, present study successfully revealed the applications of LC-DAD-ESIMS/MS, various chromatography techniques and NMR analysis to identify and characterize the polar phytochemical constituents in the butanol fraction of the methanolic C. nutans extract.